Population-based bloodstream infection surveillance in rural Thailand, 2007–2014 - Julia Rhodes; Possawat Jorakate; Sirirat Makprasert; Ornuma Sangwichian; Anek Kaewpan; Thantapat Akarachotpong; Prasong Srisaengchai; Somsak Thamthitiwat; Supphachoke Khemla; Somkid Yuenprakhon; Wantana Paveenkittiporn; Anusak Kerdsin; et al. (BMC Public Health, 2019)
Abstract Background Bloodstream infection (BSI) surveillance is essential to characterize the public health threat of bacteremia. We summarize BSI epidemiology in rural Thailand over an eight year period. Methods Population-based surveillance captured clinically indicated blood cultures and associated antimicrobial susceptibility results performed in all 20 hospitals in Nakhon Phanom (NP) and Sa Kaeo (SK) provinces. BSIs were classified as community-onset (CO) when positive cultures were obtained ≤2 days after hospital admission and hospital-onset (HO) thereafter. Hospitalization denominator data were available for incidence estimates for 2009–2014. Results From 2007 to 2014 a total of 11,166 BSIs were identified from 134,441 blood cultures. Annual CO BSI incidence ranged between 89.2 and 123.5 cases per 100,000 persons in SK and NP until 2011. Afterwards, CO incidence remained stable in SK and increased in NP, reaching 155.7 in 2013. Increases in CO BSI incidence over time were limited to persons aged ≥50 years. Ten pathogens, in rank order, accounted for > 65% of CO BSIs in both provinces, all age-groups, and all years: Escherichia coli, Klebsiella pneumoniae, Burkholderia pseudomallei, Staphylococcus aureus, Salmonella non-typhi spp., Streptococcus pneumoniae, Acinetobacter spp., Streptococcus agalactiae, Streptococcus pyogenes, Pseudomonas aeruginosa. HO BSI incidence increased in NP from 0.58 cases per 1000 hospitalizations in 2009 to 0.91 in 2014, but were higher (ranging from 1.9 to 2.3) in SK throughout the study period. Extended-spectrum beta-lactamase production among E. coli isolates and multi-drug resistance among Acinetobacter spp. isolates was common (> 25% of isolates), especially among HO cases (> 50% of isolates), and became more common over time, while methicillin-resistance among S. aureus isolates (10%) showed no clear trend. Carbapenem-resistant Enterobacteriaceae were documented in 2011–2014. Conclusions Population-based surveillance documented CO BSI incidence estimates higher than previously reported from Thailand and the region, with temporal increases seen in older populations. The most commonly observed pathogens including resistance profiles were similar to leading pathogens and resistance profiles worldwide, thus; prevention strategies with demonstrated success elsewhere may prove effective in Thailand.